Investigating the Relationship between Demographic, Radiological and Clinical Factors and In-Hospital Mortality of Non-Traumatic Subarachnoid Hemorrhage Before and After COVID-19 Pandemic - Aghamiri, Seyed Hossein; Mohamadi Khorasani, Negar; Farshadmoghadam, Hossein (Galen Medical Journal, 2025)
Background: Subarachnoid hemorrhage (SAH) is a life-threatening neurological condition that accounts for approximately 5% of all strokes. This study aimed to evaluate the demographic, clinical, and radiological factors associated with in-hospital mortality in patients with non-traumatic SAH and to assess potential differences before and after the COVID-19 pandemic. Materials and Methods: This retrospective analytical study was conducted on 177 patients with non-traumatic SAH admitted to Imam Hossein Hospital, Tehran, from November 2021 to December 2022. Diagnosis was confirmed by a neurologist using clinical presentation, imaging, and cerebrospinal fluid analysis. Patients were grouped based on discharge status (deceased vs. survived), and also classified into early- and late- pandemic subgroups based on their admission date. Comparative analyses and binary logistic regression were performed to identify predictors of in-hospital mortality. Results: Among 177 patients (mean age: 54.75 years), 36 (20.3%) died during hospitalization. Blood pressure, blood sugar, and level of consciousness at admission were significantly associated with mortality (P < 0.05), as were disease severity (Hunt and Hess grade) and angiography status (P < 0.001). No significant associations were found for age, sex, hospitalization duration, creatinine, platelets, hypertension, diabetes, or aneurysm characteristics (P > 0.05). Logistic regression identified lower Glasgow Coma Scale (GCS) scores (P < 0.001) and higher systolic blood pressure (P = 0.004) as independent predictors of mortality. Mortality was higher in the late-pandemic group (23.9% vs. 16.0%), though not statistically significant (P = 0.18). Conclusion: Lower GCS scores and elevated systolic blood pressure at admission were independent predictors of in-hospital mortality in patients with non-traumatic SAH. The COVID-19 pandemic period was associated with reduced use of angiography and a trend toward increased mortality, underscoring the importance of maintaining access to timely care during public health crises. [GMJ.2025;14:e3866] DOI:10.31661/gmj.v14i.3866